Desenvolvimento e caracterização de concretos refratários ligados quimicamente por fosfatos para aplicação em indústrias petroquímicas - Lopes, Simone Jaqueline dos Santos (Universidade Federal de São Carlos, 2017)
The objective of this work was the development of chemically phosphatebonded refractories for applications in petrochemical industries due to their suitable properties such as high green mechanical strength, erosion resistance and good adhesion. These castables also stiffen in short periods of time (~ 4h) and can be subjected to high heating rates after curing, thus reducing equipment downtime. It has been observed the lack of investigations on selfflow castables in the literature, which advantages are the easeness of application and production of pieces of complex geometries. Addictionaly it was also identified the need for products that do not require the use of binder solutions, as most commercials ones consist of two components: liquid binder (phosphoric acid) + dry mixture. Therefore, the transport and handling of monocomponent compositions are more appropriate (it can be facilitated). Two binder systems [diluted solution of H3PO4 and a mixture of H3PO4 + aluminum monophosphate (MAP)] and 4 dispersing additives, citric acid and 3 polyphosphates (Budit 3H, 6H and 8H) were tested to obtain self-flow concretes. It was found that the compositions bound with H3PO4 + MAP provided longer working time (30 min). The one with 0.5%-p Budit 3H + 0.1%-p citric acid is more promising, because it reached free flow values of 120% and thermomechanical performance higher than the reference in most of the properties. The disadvantage is that the mixture heats up to 54 °C after processing. For the vibrated castables with solid binders, MAP, sodium phosphate and magnesium monophosphate (MGP) were evaluated, and the latter contributed with promising characteristics compared to those of the commercial material. The composition containing 6%-p of this compound + 1%- p of citric acid showed workability longer than 1h and cold mechanical strength after firing at 815ºC (10.3 MPa) higher than the reference (7.9 MPa).
Development and characterization of chemically phosphate-bonded refractories castables for application in petrochemical industries
Keywords: Auto-escoante; Alumina; Monofosfato de magnésio; Self-flow; Magnesium monophosphate; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA